THE INFLUENCE OF ISLAM ON THE BEHAVIOR OF THE MUSLIM COMMUNITY IN THE LABUHAN TRADITION IN DOPLANG VILLAGE - Dian Islamiyati (MUJADDID: Journal Islamic Study and Philosophy, 2026)
The Labuhan tradition is one of the local cultural practices that continues to be preserved by communities in various regions of Indonesia. In Muslim communities, this tradition has undergone a process of adaptation and transformation influenced by Islamic teachings, resulting in a dynamic relationship between religion and local culture. This study aims to analyze the influence of Islam on the behavior of the Muslim community in preserving and practicing the Labuhan tradition in Doplang Village. The research employs a qualitative approach using a case study design. Data were collected through in-depth interviews, participant observation, and documentation involving community leaders, religious figures, traditional elders, and local residents. The collected data were analyzed using the interactive model of data reduction, data display, and conclusion drawing. The findings reveal that Islamic values have significantly shaped the attitudes and behaviors of the Muslim community toward the Labuhan tradition. Ritual elements perceived as inconsistent with Islamic teachings have gradually been replaced by religious activities such as collective prayers, recitation of the Qur'an, dhikr, and charitable acts. At the same time, cultural values such as mutual cooperation, social solidarity, gratitude, and environmental preservation continue to be maintained. The study concludes that the interaction between Islam and local tradition in Doplang Village reflects a process of cultural acculturation that strengthens religious identity while preserving local wisdom. This research contributes to the discourse on the relationship between Islam and local culture by demonstrating that religious values and cultural traditions can coexist harmoniously through adaptive social transformation.